KONTRIBUSI SEKTOR PERDAGANGAN BESAR DAN ECERAN TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA MANADO - Paulus, Yavet; Pangemanan, Sifrid S.; Pusung, Rudy J. (Universitas Sam Ratulangi, 2019)
One of the business sector that is seen as a benchmark for economic growth in a region is the trade business sector, both small trade in the form of retail and trading on a large scale. In plain view, the growing number of shops, stalls, department stores or distributors in an area can be an indication, that the flow of goods and services in the region, experienced a growth. But it needs a measurement of how much thatÂ business sector contributes to tax revenues, especially on income tax. This study is to find out how much the contribution of the large and retail trade to income tax revenues at KPP Pratama Manado beetween 2012 and 2015, before the implementation of the 2016 Tax Amnesty Law.